BELAJAR DAN MENGAJAR DALAM PERSPEKTIF AL-QUR’AN - Melinda Ratna Sari; Agustiar Agustiar; Putri Wulan Dari; Vila Sari Devi; Riyo Alfarezi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education from the Qur’anic perspective is not merely oriented toward the transfer of knowledge but also toward the development of character, spirituality, and social responsibility. However, the tendency of modern education to emphasize cognitive achievement and technical competence has created a need for a more integrative educational paradigm grounded in Qur’anic values. This study aims to analyze the concepts of learning and teaching in the Qur’an, identify the educational methods employed, explain the primary objectives of Qur’anic education, and examine their implications for contemporary education. This research employed a qualitative approach using library research. Data were collected from the Qur’an, Hadith, classical and contemporary tafsir literature, books, and relevant scholarly articles, and were analyzed through content analysis techniques. The findings reveal that the concepts of learning and teaching in the Qur’an position knowledge as a means of drawing closer to Allah and developing individuals who are faithful, knowledgeable, and possess noble character. The educational methods identified include wisdom (hikmah), good counsel (mau‘izhah hasanah), dialogue (hiwar), storytelling (qashash), and parables (amtsal), all of which contribute to the balanced development of cognitive, affective, and moral dimensions of learners. The primary objective of Qur’anic education is to cultivate the ideal human being (insan kamil) who fulfills the role of both servant of Allah and vicegerent on earth. Furthermore, the study demonstrates that Qur’anic educational values remain highly relevant in developing a humanistic, integrative, character-oriented, and adaptive educational system in response to contemporary scientific and technological advancements.